Analyzing Willingness to Pay for Improved Tap Water Quality: A Case of Kathmandu Valley of Nepal - Thapa, Arjun Kumar; Thapa, Babu Kaji (Economic Journal of Development Issues, 2020)
Solving chronic drinking water shortage problem of Kathmandu Valley has been finally achieved after arduous two decades of effort of Melamchi Water supply project. At this moment, though it is futile to ask economic worthiness of this national pride project but there is still ample room to investigate ability and willingness to shoulder such lumpy financial burden by ultimate beneficiaries of potable water in Kathmandu valley. Accordingly, this paper intends to measure and investigate the factors affecting household’s willingness to pay for improved water supply. The study enumerated 4941 households falling under Kathmandu Upatyaka Khanepani Limited (KUKL) service areas during 2015 to 2016 period. It incorporated contingency valuation (CV) tools to estimate willingness to pay by residents. We applied ordinal logistic regression model to analyze the major determinants of WTP for improved water supply system and measured different elasticity on the base of simple OLS using STATA version 12. The findings show that a third of households are headed by females, while the average family size and families per building are 5.2 and 9.6 persons respectively; all above national average. The reported major source of water by residents in the study area are Kathmandu Upattyaka Khanepani Limited (KUKL) (36%), jar water (20%), tanker (15%); and well/Kuwa and handpump (20%); while total expenditure in Nepalese Rupees (NRs) is 1314 per household per month. The willingness to pay for KUKL’s improved water by the household is NRs 404, just over 2.5 times the mean current KUKL tariff (NRs. 155) per month. The ordinal logistic regression result shows household current quantity of water utilization, price of jar water, income and perceived water quality and waterborne diseases as major determinants of WTP for improved water supply. The odds of paying higher WTP for improved water supply are significantly positive for aforementioned factors except the price of jar (which affects negatively). The income inelastic (